Pengaruh Persepsi Peserta Didik tentang PCK (Pedagogical Content Knowledge) Pendidik Fisika yang Menerapkan Kurikulum 2013 terhadap Prestasi Belajar di MAN 1 KUDUS - H M A Kumala; Fihris Fihris; Joko Budi Poernomo (Universitas PGRI Semarang, 2020)
This research is motivated by the habits of the students in addition to paying attention to the material presented also paying attention to how the educator teaches, the teaching method is combined with the learning style of the students, the result of the combination is the perception of the learning done by educators. The purpose of this study was to determine the effect of students' perceptions of PCK (Pedagogical Content Knowledge) educators who applied the 2013 curriculum on learning achievement in MAN 1 Kudus. Data collection used questionnaire method and documentation, initial analysis by validating the content instrument, and reliability test of Alpha Cronbach. Hypothesis test using simple regression analysis. The results showed the influence between students' perceptions of PCK (Pedagogical Content Knowledge) Physics Educators who applied the curriculum 2013 with learning achievements in MAN 1 Kudus very small, this was indicated by the correlation coefficient r of 0.0467, the coefficient of determination was 0, 00218 and tcount of 0.251 smaller than ttable of 2.045 (0.251 < 2.045) at the 5% significance level with N = 31 and the simple regression model formed is Y = 59.81 + 0.05X